Social Trust, Cooperation, and Human Capital - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2004)
The importance of social trust on economic growth has been suggested by many empirical works. This paper formalizes the concept of social trust and studies its formation process in a game theoretic setting. It provides plausible explanations for a wide range of empirical and experimental findings. The main results of the paper are as follows. For utility-maximizing players, cooperation arises in one-period prisoner’s dilemmas if and only if there is social trust. The amount of social trust in a given game is determined by the distribution of players’ cooperative tendency. Cooperative tendency is in essence a component of human capital distinct from cognitive ability. Its investment, however, is typically not efficient because the social returns are always strictly larger than individual returns. This positive investment externality leads to multiple equilibria in social trust formation, but a unique stable equilibrium may also exist. The different effects of legal institutions, information structure and education programs on social trust are also investigated.